2010
DOI: 10.1519/jsc.0b013e3181cc26b9
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Sessionrating of Perceived Exertion Method for Quantifying Training Load in Teamgym

Abstract: Teamgym is a new and emerging closed-skill sport, which includes tumbling, trampette, and floor programs performed by teams ranging from 6 to 12 athletes. The purpose of this study was to verify the concurrent validity of the session-rating of perceived exertion ([RPE] session-RPE) to quantifying the internal training load (ITL) of tumbling, trampette, and floor training sessions using Edwards' summated heart rate (HR)-zone method as a criterion measure. Session-RPE was obtained with 2 different instruments (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…32 Because of its simplicity, sRPE (which was anticipated by Gastin contemporaneously with first publication of sRPE 31 and used to plan and periodize the training of Australian Football players) has become widely used. [33][34][35][36][37] Because of the simplicity of sRPE, it has been possible to use it to analyze the data derived to examine the relationship between training load and performance 5 and to demonstrate that derived variables such as monotony and strain contribute to maladaptive responses to training. 38 There has been interest for many years in whether responses during submaximal exercise could serve as surrogate markers of how Figure 4 -Schematic of running speed versus heart rate (HR) and blood lactate.…”
Section: The Presentmentioning
confidence: 99%
“…32 Because of its simplicity, sRPE (which was anticipated by Gastin contemporaneously with first publication of sRPE 31 and used to plan and periodize the training of Australian Football players) has become widely used. [33][34][35][36][37] Because of the simplicity of sRPE, it has been possible to use it to analyze the data derived to examine the relationship between training load and performance 5 and to demonstrate that derived variables such as monotony and strain contribute to maladaptive responses to training. 38 There has been interest for many years in whether responses during submaximal exercise could serve as surrogate markers of how Figure 4 -Schematic of running speed versus heart rate (HR) and blood lactate.…”
Section: The Presentmentioning
confidence: 99%
“…R esults indicate that session ratings of perceived exertion (SRPE) is a versatile marker of training load that can provide valid estimates of training loads during activities that are intermittent in nature (6,11,(17)(18)(19) or that vary in technical difficulty of complex motor skills (17,18). Moreover, SRPE has been demonstrated to be sensitive to changes in intensity (measured by percentage 1 repetition maximum [1RM]) (4,16,23,25) and total work during resistance exercise training to failure (21).…”
Section: Introductionmentioning
confidence: 99%
“…Engelmann et al showed that breaks during complex laparoscopic surgery reduced psychological stress maintaining efficiency without prolonging operating time [5]. In athletics, Borg CR10 is used to score and plan the methodology of training [15]. This helps to decide the optimal time spent in training as low-level sustained muscular activity results in musculoskeletal pain [16].…”
Section: Discussionmentioning
confidence: 99%